Influences on Gen Z’s Financial Choices in Pokhara: Drivers of Money Management Behaviour - Adhikari, Nabin Bahadur; Adhikari, Bipin Bahadur; Poudel, Resam Lal (Journal of Business and Management, 2025)
Objectives: This paper examines the factors of personal financial management behaviour among Gen-Z and analyzes the relationship and impact of those driving forces on the money management behaviour of the same generation in Pokhara Metropolitan City.Materials and Methods: It takes an exploratory research design to explore the drivers of money management behaviour. Likewise, the exploratory factor analysis has been utilized to complete the research work. Furthermore, it employs a quantitative approach to describe the variables and uses a causal comparative research design to examine the link and impact between the variables.  Data were collected by using a structured questionnaire from a sample of 384 people of the Gen Z category in Pokhara Metropolitan City by following the idea of Cochran (1977). The dual method ‘drop and collect’ and the Google form were used to accumulate the data. Results: The four major constructs were identified based on EFA. This study found that there is a significant positive relationship between driving forces and MMB.  Regression analysis further confirms that LoC, FinL, and FinK have a significant positive effect and are considered as major drivers for the personal money management behaviour, whereas FinS is a negative driver for the personal money management behaviour of Gen-Z. About 63% can be explained by the four identified variables.Conclusion: The driver for the personal money management behaviour of Gen-Z is Locus of control, followed by Financial Literacy, and a negative driver, according to finding is Financial Stress. About 63% can be explained by the four identified variables through EFA, which may stimulate the upcoming researcher to conduct further research in this area.